Reflections on the assessment of student learning in Special Education at Basic Education - Maria Sylvia Cardoso Carneiro (Universidade Federal de Santa Maria (UFSM), 2012)
This text reflects on special education student's accomplishment at basic education level, focusing on issues concerning the assessment of learning. Educational policies from an inclusive perspective have guided education systems to develop strategies with the purpose to include these students in school life. This means recognizing them as subjects of learning, taking into account their limitations, but also their possibilities and especially their peculiarities and the different ways of learning and teaching resulting from that. For special education to be effective as an inclusive perspective, pedagogical practices in school at basic education level should be organized collectively in school, always preserving the role of the coordinating teacher in conducting the schooling processes for all students. However, this is not the dynamics found in most schools. The presence of students with disabilities in regular education schools further tightens discussions on the evaluation of learning, which will always be a task assigned to the coordinating teacher, the one who planned the teaching/learning process. Without ignoring the importance of specific accessibility resources to physical space and communication, as well as of adapting teaching materials to the needs of each student, it is important to consider that the education process for these subjects cannot be limited to the elimination of barriers, whether physical, communicational, informational or attitudinal. It is essential that the priorities of school pedagogical practices include the ownership of the historically produced knowledge on behalf of all students. For such empowerment to materialize, it is necessary to perform a teaching work articulated among different school professionals.